Assessment of medication therapy adherence in glaucoma: scoping review - Rosu, Amalia Mihaela (2020)
Introduction: Glaucoma is an asymptomatic disease, which can cause irreversible blindness, with a worldwide prevalence of around 64.3 million people. Adherence to glaucoma treatment is crucial to control the disease and to prevent its complications. Low medication adherence results in visual loss, which can lead to irreversible blindness. In this sense, it is important to know and evaluate adherence to pharmacological therapy among patients with glaucoma. Areas covered: A scoping review was conducted, according to the methodology proposed by Arksey and O’Malley. The databases used were Medical Literature Analysis and Retrieval System Online (MEDLINE) and the Biblioteca do Conhecimento Online (B-on). Our research used as primary sources articles in Portuguese and English. Expert opinion: The identified adherence rates were very different, and the conditions of how under medication adherence was assessed were highly variable. These conditions impossibilities a proper comparative study. Further efforts are needed to increase health literacy and thus identify and support patients with low medication adherence rates. It is important that health care personnel could improve patients’ knowledge about the importance of medication adherence, glaucoma disease, and the consequences that result from a lack of treatment.